Session rating of perceived exertion is different for similar intensity and duration prescribed low-intensity sessions and has a different effect on performance in young cross-country skiers - Pind, R.; Purge, P.; Mäestu, E.; Vahtra, E.; Hofmann, P.; Mäestu, J. (The Journal of Strength and Conditioning Research, 2023)
The aim of this study was to analyze whether the rating of perceived exertion (RPE) and the resulting internal load (sRPE) could differ among subjects when volume and intensity are matched in young cross-country (XC) skiers. Second, we analyzed whether subjects with a high or low RPE response and sRPE have different adaptation after a 1-week low-intensity high-volume training period. Well-trained national level XC skiers (n = 13) aged 13.4 ± 1.9 years took part in a 1-week training period with double poling performance tested pretraining and after 1-week training. All subjects trained under a similar training program. Rating of perceived exertion was measured after each training session on a 10-point scale, and the total training load was calculated by the sRPE method by multiplying training session's duration and the RPE. Subjects were divided into Glow (n = 6) or Ghigh (n = 7) groups based on median rating of RPE (3.78 ± 1.24) in low-intensity trainings. Total training load in low-intensity trainings was higher in Ghigh compared with Glow (4,010 ± 765 vs. 2,499 ± 193 arbitrary units, respectively), although total training time with (16.3 ± 0.8 hours vs. 16.0 ± 0.6 hours) or without (13.1 ± 0.9 hours vs. 13.3 ± 0.7 hours, p > 0.05, respectively to Glow and Ghigh) high-intensity sessions was not different. No significant differences were found for time spent in different heart rate zones between the 2 groups. Increases in performance were significant for both groups (p< 0.05), while the effect was large in Ghigh (+12.5%; ES = 0.74), and medium in Glow (+10.7%; ES = 0.34). Differences in the internal load and the further quantification of training load for different target intensity sessions could provide important practical information to stimulate expected adaptation in young endurance athletes.